2022
DOI: 10.3390/ma15248938
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Static and Dynamic Characteristics of Recycled Waste Tire Rubber Particle–Cement–Sand Composite Soil

Abstract: To investigate the static and dynamic characteristics of rubber–sand composite soil (RS soil) reinforced with cement, a series of triaxial compression tests and resonant column tests was performed by considering the influence of rubber content (10%, 20%, 30%, 40%, and 50%), cement content (0, 1.5, 2.5, 3.5 and 4.0 g/100 mL), and effective consolidation confining pressure (50, 100, and 150 kPa). Compared with the RS soil, the addition of cement significantly improved the shear strength of a cement–rubber–sand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A similar study was performed on clay soils, and the results showed an improvement in the permeability and resistance behaviour of poor clay soils [102,103]. In addition, there have been several recent studies exploring the use of raw GTR mixtures [104] and the use of cement-GTR [105] or mortar-GTR mixtures [106] in expansive clay soils. These studies have shown significant improvements in the geotechnical properties and stability of expansive clay soils, one of the major problems in building foundations.…”
Section: General Civil and Building Construction Usesmentioning
confidence: 77%
“…A similar study was performed on clay soils, and the results showed an improvement in the permeability and resistance behaviour of poor clay soils [102,103]. In addition, there have been several recent studies exploring the use of raw GTR mixtures [104] and the use of cement-GTR [105] or mortar-GTR mixtures [106] in expansive clay soils. These studies have shown significant improvements in the geotechnical properties and stability of expansive clay soils, one of the major problems in building foundations.…”
Section: General Civil and Building Construction Usesmentioning
confidence: 77%